The marketised university and the politics of motherhood - Amsler, Sarah; Motta, Sara C. (Taylor & Francis, 2017)
In this paper, we offer a critique of neoliberal power from the perspective of the gendered, sexualised, raced and classed politics of motherhood in English universities. By using dialogical auto-ethnographic methods to examine our own past experiences as full-time employed mother–academics, we demonstrate how feminist academic praxis can not only help make the gendered workings of neoliberal power more visible, but also enable us to nurture and sustain alternative ways of being and working in, against and outside the university. Far from desiring greater inclusion into a system which enshrines repressive logics of productivity and reproduces gendered subjectivities, inequalities, silences and exclusions, we aim to refuse and transgress it by bringing feminist critiques of knowledge, labour and neoliberalism to bear on how we understand our own experiences of motherhood in the academic world.